CHALLENGES OF USING TECHNOLOGIES IN TEACHING AND LEARNING PROCESS OF MARITIME ENGLISH STUDIES IN NEW NORMAL ERA - Rahmawati, Yusi (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Digital English Learning and Technology nowadays are the best combination during COVID – 19 pandemic era. When all the people in the world cannot do their life normally as a tone as the learning activities in the entire world, a teacher also cannot meet their students as well in the real life, in face to face teaching learning activities. Even it is not an easy thing for some people in the world to have an online classroom because of their economy problems behind, but health is also the most important one to be kept especially for their children. As a teacher, this new – normal era also still become a struggle in running their teaching learning activities. Teachers also face many problems in delivering the right material to be achieved as well to their students at home. Besides that, delivering materials is the teacher’s responsibility. In the same line, lecturers in higher level of education also face similar problems. Lecturers try to use several technologies to grab the capabilities of the students in receiving the material through online classroom. It is not as simple as some people think. Maritime English lecturers have many challenges in doing their online classroom because they should deliver some English skills as well to their students at home also to follow the government instruction during this pandemic era. In this research, the writer uses a case study to delve the problems faced by the lecturers especially maritime English lecturers in delivering their materials through online classroom. The finding of this research is the writer meets some difficulties in maritime English lecturers in running their online classroom.